2013
DOI: 10.12809/hkmj133601
|View full text |Cite
|
Sign up to set email alerts
|

The role of high-sensitivity C-reactive protein for assessing coronary artery disease severity and left ventricular end diastolic pressure in patients with suspected coronary artery disease

Abstract: High-sensitivity C-reactive protein level is a clinical parameter that could predict left ventricular end diastolic pressure and left ventricular dysfunction, but was not associated with the severity of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Various studies have indicated hs-CRP as a predictor of cardiovascular events such as myocardial infarction, stroke, peripheral vascular obstruction among apparently healthy men and women as well as the elderly and smokers [ 21 – 23 ]. Rashidinejad and colleagues concluded that high-sensitivity CRP level is a clinical parameter that was not associated with the severity of coronary artery disease [ 24 ]. Several investigations in healthy as well as high-risk individuals have demonstrated a relationship between CRP and the risk of coronary artery disease (CAD) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have indicated hs-CRP as a predictor of cardiovascular events such as myocardial infarction, stroke, peripheral vascular obstruction among apparently healthy men and women as well as the elderly and smokers [ 21 – 23 ]. Rashidinejad and colleagues concluded that high-sensitivity CRP level is a clinical parameter that was not associated with the severity of coronary artery disease [ 24 ]. Several investigations in healthy as well as high-risk individuals have demonstrated a relationship between CRP and the risk of coronary artery disease (CAD) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein (CRP) is a sensitive, nonspecific marker of inflammation, which is elevated, among other things, as an effect of the activity of several cytokines. High-sensitivity C-reactive protein (hsCRP) measurement is used for cardiovascular risk estimation, mainly a risk of acute coronary events [19,20,25]. CRP concentration depends on many factors, such as gender, age, body mass, smoking, and physical activity [3,17].…”
Section: Introductionmentioning
confidence: 99%